Dr. Patangi Rangachari: Finding the Right Mental Country - Amjad, Humna; Chopra, Shelly; Ostrovski, Ilia (The Meducator, 2013)
The Meducator recently sat down with Dr. Patangi Rangachari, Professor (Emeritus) of Medicine at McMaster University and 3M National Teaching Fellow, to discuss his experiences as a professor and his perspective on health professional education. From his policy of “drift” to the notion of a “pluripotent student”, Dr. Rangachari emphasized that students should be in no rush to make their career choice. He shared his insight into the purpose of learning and described the potentially detrimental effects of not choosing the right “mental country”.